2022
DOI: 10.3390/s22031196
|View full text |Cite
|
Sign up to set email alerts
|

Smart Eyeglasses: A Valid and Reliable Device to Assess Spatiotemporal Parameters during Gait

Abstract: The study aims to determine the validity and reproducibility of step duration and step length parameters measured during walking in healthy participants using an accelerometer embedded in smart eyeglasses. Twenty young volunteers participated in two identical sessions comprising a 30 s gait assessment performed at three different treadmill speeds under two conditions (i.e., with and without a cervical collar). Spatiotemporal parameters (i.e., step duration and step length normalized by the lower limb length) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…During the 6MWT, participants had to cover the greatest possible distance in 6 min, without running, in a 10 m shuttle. Besides the total distance obtained from the number of shuttles performed [ 18 ], two previously validated spatiotemporal parameters were collected with the smart eyeglasses [ 36 ]. During offline analysis, step duration was first calculated from each step, represented by the temporal difference between two consecutive maximal vertical acceleration peaks recorded by the smart eyeglasses’ IMU.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the 6MWT, participants had to cover the greatest possible distance in 6 min, without running, in a 10 m shuttle. Besides the total distance obtained from the number of shuttles performed [ 18 ], two previously validated spatiotemporal parameters were collected with the smart eyeglasses [ 36 ]. During offline analysis, step duration was first calculated from each step, represented by the temporal difference between two consecutive maximal vertical acceleration peaks recorded by the smart eyeglasses’ IMU.…”
Section: Methodsmentioning
confidence: 99%
“…Although most of the studies placed the IMUs close to the body’s center of mass or at the wrist [ 32 ], some studies have suggested that head-level placement improves movement accuracy for fall detection compared to wrist [ 33 ] or hip and trunk [ 34 ] placements. In this context, connected smart eyeglasses have been developed and validated to monitor Sit-to-Stand movements and spatiotemporal parameters during walking in healthy young participants [ 35 , 36 ]. However, to date, smart eyeglasses embedding an IMU have not been used to assess the functional physical capacities of older adults.…”
Section: Introductionmentioning
confidence: 99%
“…The so-called smart glasses or smart spectacles describe a type of head-don display technology that functions as a computer and aids users to access information within their visual field of view in realtime [35]. According to Hellec et al, most elderly people wear glasses during daily living activities, embedding an IMU in such a wearable device of daily utility could portend a technological innovation for gait analysis [36].…”
Section: Smart Spectaclesmentioning
confidence: 99%
“…Both sonographers were unaware of the histopathology results. The intra-and interobserver concordance was assessed using the interclass correlation coe cients (ICCs), and ICCs greater than 0.75 indicated good stability of the features (Hellec et al 2022).…”
Section: Feature Extractionmentioning
confidence: 99%